Prospective Evaluation of Health After Breast Reduction Surgery Using the Breast-Q, Short-Form 36, Breast-Related Symptoms Questionnaire, and Modified Breast Evaluation Questionnaire. Issue 2 (August 2019) - Lewin, Richard; Lidén, Mattias; Lundberg, Jonas; Hansson, Emma; Selvaggi, Gennaro; Thorarinsson, Andri; Elander, Anna
Abstract : Introduction: Breast hypertrophy is a condition associated with physical, psychological, and psychosocial problems. The primary aims of this study were to determine the impact of breast hypertrophy and the effects of breast reduction, performed on the basis of well-described inclusion criteria, on general and breast-related health, using both general and diagnosis-specific validated questionnaires. We used a prospective, longitudinal paired study design. A secondary aim was to analyze the relationship between preoperative breast volume, body mass index, sternal notch-to-nipple distance and the weight of resected tissue on the one hand and improvements in health on the other. Methods: Three hundred forty-eight consecutive patients undergoing breast reduction were included and the Short-Form 36 (SF-36), Breast-Related Symptoms Questionnaire (BRSQ), Modified Breast Evaluation Questionnaire (mBEQ) and BREAST-Q were distributed preoperatively and 1 year postoperatively. Results: A total of 284 (83%) patients answered the questionnaires either preoperatively or postoperatively, or both, and 159 (46%) patients answered both. The breast hypertrophy patients had significantly lower scores preoperatively than the matched normal population when it came to all dimensions of the SF-36 and mBEQ. The preoperative scores for both the BRSQ and BREAST-Q were low. After breast reduction, there were significant improvements in all dimensions of the BRSQ, mBEQ, and Breast-Q and in several dimensions of the SF-36. Conclusions: Breast reduction reduces or removes disease-associated pain. It improves or normalizes perceived health and psychosocial self-esteem in slightly obese women or women of normal weight with preoperative breast volumes around 1000 mL. Women with higher preoperative breast volumes and longer sternal notch-to-nipple distances appear to be more satisfied with the cosmetic result postoperatively.